Komunikasi Antar Budaya Masyarakat Suku Jawa dengan Masyarakat Asli di Desa Pulau Semambu - Shaputra, Doni Febrian; Razzaq, Abdur; Apriko, Syendi (Indonesian Journal Publisher, 2025)
This study focuses on intercultural communication between the Javanese and indigenous people in Pulau Semambu Village. Pulau Semambu Village is an area with high cultural diversity, where the Javanese live side by side with the local indigenous people. The purpose of this study is to analyze cultural assimilation, communication patterns, obstacles, and efforts made to bridge cultural differences between the two tribes. The research method used is qualitative with an ethnographic approach, data collected through observation, interviews, and documentation. This study concludes that intercultural communication in Pulau Semambu Village plays an important role in creating social integration amidst cultural diversity. Open interaction and intercultural dialogue are the main keys to building harmonious relationships. The results of this study are expected to be a reference for the development of intercultural communication strategies in other multicultural societies.